Women workers and gender identities, 1835-1913 : the cotton and metal industries in England / Carol E. Morgan. - Morgan, Carol E. (Women's and gender history, 2001)
This work examines the experiences of women workers in the cotton and small metals industries and the discourses surrounding their labour. It demonstrates how ideas of womanhood often clashed with the harsh realities of working-class life.